Proportional drawing aid / Issarezal Ismail ... [et al.] - Ismail, Issarezal; Che Yaacob, Muhammad Najibul Muthie; Mazlan, Hilal; Abdul Razak, Ruzamira; Razali, Rosmidahanim; Said Ahmad, Siti Humaini; Roslan, Aimi Atikah; Mohd Sukeri, Nur Farhana (Universiti Teknologi MARA, Perak, 2020)
Students in the field of art sometimes don’t have ability and skills to achieve accurate proportion and arrange composition in their drawing due to lack of experiences and less of practices. They are seen hard to obtain the best focus area before starting to produce drawing and easily lose direction during artistic process because of the wide eye view. Therefore, this innovative design named Proportional Drawing Aid (PDA) was created as a tool and technology suitable for art students to compile the drawing process in the drawing class, whether implemented indoors or outdoors. The prototype design was inspired by conventional window frame method used to be held by hands but now has added added value through the innovation by combining it with eyewear to be more practical and provide comfort to its users. The prototype is produced using a 3D printing machine where the components between the window frame and eyewear can be adjusted according to the suitability of the users. The results of a study conducted on art and design students proved that the use of this tool and technology can increase the ability of students in drawing and especially in order to get accurate proportion and interesting composition.